China : AIDS Expenditure Tracking in Guangxi Zhuang Autonomous Region - China Health Economics Institute; World Bank (World Bank, Washington, DC, 2013)
The Chinese government's spending on HIV/AIDS has increased dramatically in recent years. However, it only accounts for a part of the total resources dedicated to HIV/AIDS. The fragmented nature of HIV/AIDS financing makes it difficult to register the flows of funds in a holistic and useful manner. More importantly, there are questions over the extent to which increased resources for HIV/AIDS have been allocated and utilized in an equitable and effective manner in order to achieve the intended outcomes specified in the Second Five Year Action Plan for HIV/AIDS Prevention and Control (2005-2010). This study was designed to gain a better understanding of possible impediments to an effective local HIV/AIDS response. It mainly focused on: (a) assessing different aspects of HIV/AIDS financing such as sources of financing, HIV/AIDS related services and their providers being financed, and beneficiaries; (b) estimating households out of pocket spending on HIV/AIDS; and (c) identifying bottlenecks preventing the effective and equitable utilization of existing HIV/AIDS resources.